THE USE OF SCALE MODELS AS AN ACTIVE METHODOLOGY IN ADDRESSING THE TOPIC OF WATER RESOURCES FOR ELEMENTARY SCHOOL STUDENTS AT A PRIVATE SCHOOL IN THE MUNICIPALITY OF BREVES, MARAJÓ ARCHIPELAGO - de Matos, Kildery Gomes; Gomes, Vitória Maigda Magno; Gonçalves, Benedita da Costa; de Paulo, Marcelo Almeida; Pinheiro, Eduardo Antonio Abreu; Barreiros, Rayane Pereira; Higino, Maria Emília de Oliveira (Seven Editora, 2025)
Water is a natural resource that is essential for the survival of humans, fauna, flora and the development of economic activities. Unfortunately, water resources are limited and depleted due fo human action that degrades water quality and harms ecosystems. In the process of raising environmental awareness, schools play a fundamental role in raising children’s awareness of the environment, making them citizens who are aware of their actions. In this context, the objective was to promote environmental actions with elementary school students from a private school in the urban area of the municipality of Breves through the creation of models that allowed the teaching-learning process to be effective and meaningful, since they were important tools of active methodology of Environmental Education to awaken creativity, innovation and sustainable attitudes in students and to materialize through three-dimensional forms the main topics addressed on the theme of water. DOI: https://doi.org/10.56238/sevened2025.038-064